Anxiolytic-Like Actions of Fatty Acids Identified in Human Amniotic Fluid - Rosa Isela García-Ríos; Juan Francisco Rodríguez-Landa; Carlos M. Contreras (The Scientific World Journal)
Eight fatty acids (C12–C18) were previously identified in human amniotic fluid, colostrum, and milk in similar proportions but different amounts. Amniotic fluid is well known to be the natural environment for development in mammals. Interestingly, amniotic fluid and an artificial mixture of fatty acids contained in amniotic fluid produce similar anxiolytic-like actions in Wistar rats. We explored whether the lowest amount of fatty acids contained in amniotic fluid with respect to colostrum and milk produces such anxiolytic-like effects. Although a trend toward a dose-response effect was observed, only an amount of fatty acids that was similar to amniotic fluid fully mimicked the effect of diazepam (2 mg/kg, i.p.) in the defensive burying test, an action devoid of effects on locomotor activity and motor coordination. Our results confirm that the amount of fatty acids contained in amniotic fluid is sufficient to produce anxiolytic-like effects, suggesting similar actions during intrauterine development.